JURIDICAL ANALYSIS OF JUDGE'S DECISIONS IN THE CRIME OF THREATENING AND FRIGHTENING ADDRESSED PERSONALLY - Sihombing, Lasmin Alfies (Jurnal Multidisiplin Sahombu, 2023)
In addition to having a positive impact, technology also has a negative impact on society, including the emergence of more and more new crimes, namely computer crimes, such as internet fraud, hacking of ATM PIN, burglary of banking accounts, the rise of fake social media, pornographic media, and defamation through the internet. This study aims to legally analyze the judge's decision in the criminal act of threats and intimidation directed personally related to Law Number 11 of 2008. This study uses a descriptive analysis method with a normative juridical approach. The reference for the panel of judges in deciding cases is the prosecutor's indictment, not the indictment by taking into account the evidence. The judge's considerations are deemed appropriate to be able to sentence the defendant. Regulations and sanctions for all forms of social media use must be in line with the ideals in which Law Number 11 of 2008 was made to protect and maintain the comfort of social media users. So that in the future social media users can use it wisely to build a modern and law-abiding society. In this case law enforcers must see that the use of social media is increasingly being used at this time, this causes the use of social media to become uncontrollable, causing losses to the parties.